Penerapan Metode Everyone Is Teacher Here Berbantuan Media Video Dalam Upaya Meningkatkan Aktivitas Belajar Siswa Pada Mata Pelajaran Sosiologi - Qistina Mei Sabil; Hairil Wadi; Suud Suud (Journal of Classroom Action Research, 2023)
This study aims to determine the application of the Everyone Is Teacher Here learning method assisted by Video Media in class XI IPS 2 SMAN 1 Pringgabaya. This study used classroom action research with data collection techniques through observation, interviews and documentation. The stages of this research were carried out through initial observation, planning, action, observation and reflection. The subjects of this classroom action research were students of class XI IPS 2 at SMAN 1 Pringgabaya, while the informants in the study were sociology teachers. The results of the research cycle I showed the level of student learning activities, namely oral activities (35.25%), listening activities (76.75%), writing activities (46.09%) and emotional activities (54.87%), then in cycle II shows the level of student learning activities, namely oral activities (83.49%), listening activities (90.13%), writing activities (83.96%), and emotional activities (93.45).